Anaerobic digestion of dried/shredded food waste in a periodic anaerobic baffled reactor - D. Mathioudakis; I. Michalopoulos; K. Kalogeropoulos; K. Papadopoulou; G. Lyberatos (Water Science and Technology, 2021)
The objective of the current work is to study the impact of the operational parameters' variation (HRT, OLR and T) on biomethane productivity in a periodic anaerobic baffled reactor (PABR). The feedstock used was a biomass product named food residue biomass (FORBI), which is dried and shredded source-separated household food waste. The PABR is an innovative, high-rate bioreactor. Apart from the hydraulic retention time (HRT) and the organic loading rate (OLR), an important operational parameter is the switching period (T) of the feeding compartment: when T is high, the bioreactor operation is similar to an anaerobic baffled reactor (ABR), while when it is low, the operation approaches that of an upflow anaerobic sludge blanket reactor (UASBR). Nine distinct experimental phases were conducted, during which the operational parameters of the PABR were consecutively modified: the HRT varied from 9 to 2.5 days, T between 2 days and 1 and finally the OLR from 1.24 gCOD/Lbioreactor*d to 8.08 gCOD/Lbioreactor*d. The maximum biomethane yield was 384 LCH4/kgFORBI corresponding to the operation at HRT = 5 d, OLR = 2.14 gCOD/Lbioreactor*d and T = 2 days. Similar efficiency (333 LCH4/kgFORBI) was achieved at higher OLR (4.53 gCOD/Lbioreactor*d). Highlights The feedstock used was a biomass product food residue biomass (FORBI), which is dried and shredded food waste.; Periodic anaerobic baffled reactor (PABR), a high-rate bioreactor.; The switching period (T) of the feeding compartment gives the bioreactor the element of operational flexibility.; The PABR can efficiently operate at HRTs as low as 2.5 days, however, the highest biomethane yield was achieved under HRT of 5 d.;